Book Chapter Manajemen Proyek Pada Lilou Lamp - Christina, Christina; Nelvi, Novita; Isnaeni, Dina Nur (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Lilou Lamp is a product we designed, carefully made from recycled cardboard, providing artistic and pleasant lighting. Each lamp is crafted with attention to detail and high quality, making it an environmentally friendly and stylish choice for any space. Cost analysis using Earned Value Management (EVM) is essential to understand the project's financial performance. For Lilou Lamp, the focus is on profits and the payback period. The break-even point is estimated to occur in 1.40 months. Assuming actual costs align with initial costs, the calculation of monthly profit becomes the main focus. Based on calculations, the project's break-even point and payback period are estimated to be the same, which is 1.40 months. With a monthly profit of Rp 1,233,000, the total profit for the Lilou Lamp project is Rp 1,233,000 x 1.40 = Rp 1,726,200. Thus, the expected total profit from the Lilou Lamp project is Rp 1,726,200. This analysis provides an overview of the potential profits that can be obtained from the project and helps in evaluating the project's overall financial performance. Keywords: Social Entrepreneurship, Entrepreneurship, Innovation, Sustainability, Unemployment, Job Opportunities, Project Management, Cost Analysis, Earned Value Management (EVM), Profit, Payback Period, Lilou Lamp.